A Traditional and Modern Education System of Pondok Pesantren in Perspective Philosophy of Education - Rifqi Silfiana (Islamadina : Jurnal Pemikiran Islam, 2020)
ABSTRAKPhilosophy and education have a very close relationship so that properly thinkers of philosophy respond to various problems regarding education include the education system in pesantren. This journal is intended to dissect and explore the education system of pondok pesantren both traditional and modern pesantren. Searching a philosophical foundation within it to be able to understand the deepest meaning of an education system in pesantren. Traditional pesantren organizes non-classical Islamic education with bandongan and sorogan methods in learning classical books (yellow books) by ulama in middle ages. The traditional pesantren holds the philosophy of perennialism, idealism, and essentialism. Among the famous traditional pesantren that maintain the salaf system are Sarang Rembang, pondok pesantren of Sidogiri Pasuruan, pondok pesantren of Langitan Tuban, and pondok pesantren of Lirboyo Kediri. Whereas modern pesantren always consideratein changing times such as the use of information technology with the use of the internet as a medium of learning for santri and play a role not only in education but also in other aspects. Modern pesantren holds philosophy of reconstructionism, progressivism, and rationalism. Among the famous modern pesantren are the modern pondok of Gontor and Zaitun Indramayu.